Amplificadores óticos a fibra sob um ambiente dinâmico - Freitas, Márcio (2006)
The recent advance in WDM technologies with the ability of add, drop and in effect construct wavelength-switched and wavelength-routed networks has brought a new dynamic-reconfigurable WDM network. This dynamic environment brings, besides the already well-known transmission impairments (such as chromatic dispersion, nonlinear effects, PMD, ASE, etc), a new set of impairments related to the add-drop possibilities that could severely degrade the system performance. Furthermore, the development of new optical amplifiers that could reach high output power values has also brought an increasing impact of nonlinear effects in the signal propagation at different applications. The optical fiber amplifiers presented in the study are the erbium-doped fiber, the ytterbiumdoped fiber amplifier, the erbium-ytterbium codoped fiber amplifier and the Raman fiber amplifiers. For this study, appropriate numeric models for each amplifier were implemented. This work investigates by numerical simulation how the optical fiber amplifiers and consequently the system performance are affected by the dynamic-reconfigurable traffic. Some contributions about the study of the power transient evolution generated by the optical amplifiers in different transmission bandwidths, under different amplifier configurations and in different applications are presented. It is also presented a contribution for the optimization of control methods to minimize the power transients generated by the optical amplifiers due the add-drop of channels in the system. Moreover, this work also analyzes the impact of high powers generated in the amplification process, and presents some contributions for the study of the nonlinear effects in the signals propagation through the amplifier.